Can pollen match shoes to a previously visited indoor location?. Issue 2 (2nd April 2016) - Nguyen, Philipp; Weber, Martina
Abstract: This paper is part of an investigation dedicated to indoor pollen from a forensic point of view. Previous studies documented the 'natural' pollen content of a flat and how it was 'artificially' altered by ornamental plants. The present study investigated if this 'artificial pollen trace' can be transferred to shoes. Brand new sneakers were worn in the flat and afterwards examined for pollen on their soles. The results showed that the shoes gathered pollen and that some pollen types correlated to those found in the flat. Afterwards, some of these shoes were worn while walking through the city for approximately 1.8 km. On these shoes, flat pollen was also detectable, but in low abundances. This study shows that, from a palynological point of view, shoes are worth a look at when a crime is investigated. Uncommon pollen grains on shoes can point to an indoor location with the corresponding ornamental plants.